A novel double-helical-kernel evolution pattern of gold nanoclusters: alternate single-stranded growth at both ends. Issue 11 (30th January 2017) - Dong, Hongwei; Liao, Lingwen; Zhuang, Shengli; Yao, Chuanhao; Chen, Jishi; Tian, Shubo; Zhu, Min; Liu, Xu; Li, Lingling; Wu, Zhikun
Abstract : Two novel gold nanoclusters were synthesized and structurally resolved, and a novel double-helical-kernel evolution pattern of gold nanoclusters was observed. Abstract : Studying the kernel evolution pattern of gold nanoclusters is intriguing but challenging due to the difficulty of precise size control and structure resolution. Herein, we successfully synthesized two novel gold nanoclusters, Au34 (S-c-C6 H11 )22 and Au42 (S-c-C6 H11 )26 (S-c-C6 H11 : cyclohexanethiolate), and resolved their structures. Interestingly, it was found that the kernel evolves from Au28 (S-c-C6 H11 )20 to Au34 (S-c-C6 H11 )22 and Au42 (S-c-C6 H11 )26 in a novel fashion: alternate single-stranded evolution at both ends, which is remarkably different from the reported double-stranded growth at the bottom for the 4- tert -butylbenzenethiolate (TBBT)-protected nanocluster series. This work illustrates the variety of kernel evolution patterns and the directionality of the ligands with respect to the evolution of the kernel. In addition, differential pulse voltammetry (DPV) revealed that the electrochemical gap between the first oxidation and the first reduction potential decreases as the size increases from Au28 (S-c-C6 H11 )20 to Au34 (S-c-C6 H11 )22 and Au42 (S-c-C6 H11 )26 .